Politicians’ priorities and the determinants of priorities in the Swedish social services - Marie Wörlén (Nordic Journal of Social Research)
The setting of priorities is an integrated part of social-work politics in Sweden as well as internationally. This article explores Swedish social services and how politicians on the political boards wish to make priorities and what these priorities involve. The use of regression analyses also reveals which circumstances are of importance for allocative precedence and the impact different distributive principles have. It is hard to detect clear-cut patterns of circumstances that guide the judgements in any one direction. The results show that political affiliation overall is not a determining factor for attitudes towards how priorities are made. Another result is a manifest area bias, suggesting that respondents tend to see to the interests of their own professional domain, a result most visible among the politicians involved with Care for the Elderly and Disabled (CED). Yet, with regard to allocative principles, political colour seems to matter. Conservative politicians, as expected, agree with the principles of economy and of capacity to benefit, while the socialist block, less expectedly, seems to embrace the principle of deservingness.